A Little Peek May Be Enough: How Small Hive Beetle Estimates Can Help Address Immediate Colony Management Needs - Ethel M. Villalobos; Luis Medina Medina; Zhening Zhang; Scott Nikaido; Emanuel Miranda; Jason Wong; Jessika Santamaria; Micaela Buteler (Insects)
Due to the ongoing global spread of the small hive beetle (SHB), Aethina tumida, there is a significant need for detection and practical management strategies against this pest. The standard inspection strategies for SHBs involve (1) detailed visual examination of the colony, which is challenging in areas with defensive bees, or (2) sampling beetles via traps, which requires repeated visits to the apiary and can be difficult for beekeepers with apiaries in rural areas. In this study, we modified the inspection sequence to examine the in-hive distribution of the beetle and assess whether a limited, yet targeted, inspection could provide valuable information on beetle infestation. We conducted our modified sampling in three different countries: Hawai’i (USA), Mexico, and Costa Rica. We found that targeted screening of the top areas of the hive (cover and top-side frames) provided reliable information about the relative prevalence of SHBs in a colony. The results also suggested that SHBs do not naturally congregate on a bare bottom board but migrate downward during inspection. Trap placement on the bottom floor of the hive may underestimate beetle presence in low to medium pest levels. The proposed inspection protocol is not influenced by the genetic origin of the bees (Africanized or European) and could be a practical alternative for assessing SHB infestation levels in honeybee colonies.